AGAMA DAN KEBERAGAMAAN: SEBUAH KLARIFIKASI UNTUK EMPATI - Haris (Al'Adalah, 2013)
The nature of religion has been endlessly discussed by philosophers, theologians, psychologists, and sociologists. They look at different aspects of religion as their interests and their purposes differ. Therefore, they formulate variety of definition of religion. Religion is seen to be difficult to define. But it is necessary to have a clear definition of religion as a starting point for religious studies. This paper discuss the definitions of religion given by the schoolars and then give a clear definition as an attemp to build up tolerant. Religion is not the same with religious beliefs and practices or religious experiences.